Monitored Anesthesia Care in Uterine Artery Embolization for Leiomyomas and Adenomyosis - Jiah Oh; Chang-Woon Kim; Moon Ok Lee (Clinical and Experimental Obstetrics & Gynecology)
Background: Patients undergoing an interventional radiology procedure report some degree of anxiety. Therefore, procedure-related anxiety needs to be managed. The aim of our study was to investigate patient satisfaction with monitored anesthesia care (MAC) for uterine artery embolization (UAE)-related procedural anxiety in symptomatic uterine fibroids or adenomyosis. Methods: Between May 2021 and June 2022, 36 patients with symptomatic fibroids or adenomyosis underwent UAE with MAC. Follow-up evaluations consisted of clinical symptoms, degree of satisfaction with MAC in UAE, and complications. Results: MAC in UAE was successfully performed in all patients. UAE significantly reduced patients’ complaints such as bleeding and pain: the scores for bleeding and pain were significantly reduced after 3 months of UAE compared with those before UAE, indicating the effectiveness of UAE. The mean score of satisfaction with MAC in UAE was 4.3 points, meaning that 94.4% of women were satisfied or very satisfied. No major complications were observed. Conclusions: MAC in UAE for symptomatic uterine fibroids or adenomyosis can be emotionally effective and safe for patients who are anxious about the procedure.